The Improved Photocatalytic Properties of Methylene Blue for V2O3/CNT/TiO2 Composite under Visible Light - Ming-Liang Chen; Won-Chun Oh (International Journal of Photoenergy)
Multiwall carbon nanotube (MWCNT), vanadyl acetylacetonate (V(acac)3), and titanium n-butoxide (TNB) were used as carbon, vanadium oxide, and titanium oxide precursor to prepare V2O3/CNT/TiO2 composite. The obtained composite was characterized by BET surface area measurement, X-ray diffraction, transmission electron microscopy, and energy dispersive X-ray analysis. In addition, we used methylene blue (MB) solution under condition of visible light irradiation to determine their photocatalytic degradation efficiency. In conclusion, the V2O3/CNT/TiO2 composite had excellent photocatalytic degradation for MB solution under visible light.